Exploring the lived experiences of postbasic nursing students: insights into continuous learning - Aung, Khin Thandar; Mohd Ali, Noor Azizah; Mohd Mokhtar, Hanida Hani; Atan, Ashikin; Mohd Noh, Hairanni; Ahmad, Sarina (Penerbit USM, 2024)
Continuous learning in clinical settings is essential for optimum quality of care. This study examines the lived experiences of post-basic nursing students specialising in critical care, emergency care, and peri-operative care in a tertiary university hospital. Using a descriptive phenomenological approach, three focus group interviews were conducted with 23 purposively sampled post-basic critical care nursing students. Four overarching themes emerged from the data analysis: (1) the programme’s benefits to students; (2) feedback on programme implementation; (3) avenues for future improvement; and (4) challenges encountered during the programme. The findings emphasise the critical role of ongoing education in clinical contexts, particularly in post-basic critical care nursing education. Students’ lived experiences underscore the programme’s positive effects on their knowledge, skills, and organisational benefits, emphasising the crucial role of continuous education in enhancing the quality of nursing care. The identified themes offer valuable insights into the advantages, obstacles, and areas needing improvement in post-basic critical care nursing education. They showed the importance of a sustained commitment to continuous learning to ensure the delivery of high-quality care in clinical practice. This study contributes to the existing body of knowledge on nursing education and offers valuable insights for educators, administrators, and policymakers to optimise the training and development of nurses to achieve quality patient outcomes.